Isika Tanah Pada Lahan Marginal: Strategi Pengelolaan Untuk Produktivitas Pertanian - Waruwu, Reflesia Juni Arsanti; Waruwu, Henki Darman (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This study aims to evaluate the effect of soil amendments on the fertility and productivity of marginal land. The method used is an experiment with a completely randomized design (CRD) involving several treatments, namely no soil amendment (control), compost addition, green manure, biochar, and lime. The results show that all soil amendment treatments increased the soil pH, organic matter content, and cation exchange capacity (CEC). The compost treatment produced the highest productivity, with an average plant height of 90 cm, 20 fruits per plant, and a harvest weight of 2.5 kg per plant. This study concludes that soil amendments, especially compost and biochar, significantly contribute to improving the fertility and productivity of marginal land, offering sustainable solutions for agricultural management.